Internal Audit Function and Audit Fees: Evidence from Nigeria - Ali, Muqaddam Oyetunji; Wan Abdullah, Wan Amalina (Institut Agama Islam Negeri Kendari, 2021)
The purpose of this study is to analyse the relationship between audit fees and internal audit function in the Nigerian listed companies. This study observes 60 non-financial firms over four years (2012 to 2015) and uses random effect regression model to examine the hypothesis. The result of the study found internal audit to be significantly related with amount of audit fees paid by the listed firms. Specifically, this study found internal audit expertise and size of internal audit unit to have a positive and significant relationship with audit fees while no relationship was documented between internal audit certificate and the amount of audit fees. The study concludes that company with effective and adequate internal audit unit tend to pay higher audit fees to the external auditors.